Sensation of laryngeal obstruction as a manifestation of myocardial infarction: A case report - Zhuanbo Luo; Hequn He; Xueqin Chen (Journal of International Medical Research, 2021)
A rare case of a 62-year-old woman with an atypical cardiac symptom of sensation of laryngeal obstruction as a manifestation of acute coronary syndrome is described. Initially, the patient showed unremarkable test results and was diagnosed with laryngopharyngitis and discharged from hospital. However, 24 hours later she returned to the hospital with an abnormal electrocardiogram (ECG) and elevated blood troponin levels and was diagnosed with ST-segment elevation myocardial infarction (STEMI). She developed heart failure, cardiogenic shock and died. Clinicians should be aware that patients with an unexplained sensation of laryngeal obstruction should be considered for the presence of MI within their differential diagnosis since this may be the only symptom in some patients with life-threatening cardiac ischemia.